2000
DOI: 10.1117/12.404789
|View full text |Cite
|
Sign up to set email alerts
|

<title>HOEs for producing specific light patterns in the near field</title>

Abstract: considers the methods of computation and fabrication of focusing phase optical elements that operate in the visible spectral range and produce specific light patterns iii the near field. We determine the relationship between the dimension of the quantization grid used in computations and the performance of the optical elements and parallieters of corresponding light patterns. The paper gives the results of computation of I D and 21) H( )Es and describes the fabrication methods and experimental samples.Correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In more general case complex images can be formed in a focal plane. Such structures are not realized by methods of traditional optics, however they can be created with the help of artificial computer synthesised holograms [1]. The opportunity of association of many multifocal phase CGH in a continuous raster is shown that is important for systems of parallel information processing and for complex images formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more general case complex images can be formed in a focal plane. Such structures are not realized by methods of traditional optics, however they can be created with the help of artificial computer synthesised holograms [1]. The opportunity of association of many multifocal phase CGH in a continuous raster is shown that is important for systems of parallel information processing and for complex images formation.…”
Section: Introductionmentioning
confidence: 99%
“…In course of synthesis of such rasters the problem of union of image fragments formed by separate CGH and elimination of interbeam interference is solved. Calculation of phase multifocal CGH is carried out using Fourier approximation of diffraction in the near field [1,2]. At computer synthesis of the hologram both the phase structure, and complex amplitude-phase distribution in a focal plane are set on the bidimentional discrete grid of ɆɯɆ readouts.…”
Section: Introductionmentioning
confidence: 99%